The structure of polymer carriers controls the efficacy of the experimental combination treatment of tumors with HPMA copolymer conjugates carrying doxorubicin and docetaxel - Šírová, Milada; Strohalm, Jiří; Chytil, Petr; Lidický, Ondřej; Tomala, Jakub; Říhová, Blanka; Etrych, Tomáš (Journal of controlled release, 2017)
The tumor-specific targeting of cancerostatics using polymer drug carriers represents a potential strategy to achieve an effective treatment with reduced side toxicity. Synthetic water-soluble copolymers based on N-(2-hydroxypropyl)methacrylamide (HPMA) are carriers with tunable architecture and drug loading, tumor-specific accumulation of the drug, and its controlled release. We describe a combination treatment of murine EL4 T cell lymphoma with HPMA-based star conjugates (Mw 250,000gmol-1) of doxorubicin (Dox) or docetaxel (Dtx) designed for enhanced tumor accumulation and combination therapy. Although the combination of linear conjugates (Mw=28,000gmol-1) containing Dox or Dtx resulted in an additive effect in the treatment of the lymphoma, the opposite was observed in the combination of two star conjugates with Dox or Dtx, as the star Dtx conjugate decreased the treatment efficacy of the star Dox conjugate. The Dtx conjugate alone was virtually ineffective in the reduction of tumor growth or survival time extension; thus, a curative effect could be solely attributed to the Dox-containing conjugate. When Dtx was delivered to the tumor on the same polymer carrier as Dox, the efficacy of the Dox-induced treatment was reduced to a lesser extent. No reduction was found when Dtx was delivered by a linear polymer or applied as a free drug. The phenomenon was strictly related to the enhanced permeability and retention (EPR) effect, as it was not observed in BCL1 leukemia, a model without EPR. The diminished treatment outcome in the combination therapy with the two star conjugates was underlined by the significantly decreased accumulation of Dox in the tumor. The use of the drug-free polymer carrier instead of the Dtx-containing star conjugate did not reduce the treatment efficacy of the Dox conjugate. Thus, the physicochemical characteristics of the polymer carrier designed for tumor-specific drug delivery systems control the activity of the respective drug, leading to changes within the tumor microenvironment that can determine ultimate efficacy of the combination therapy.
Keywords: doxorubicin; docetaxel; protinádorové látky; Neoplasms; Cell Line, Tumor; EPR effect; Taxoids; Acrylamides; myši inbrední BALB C; Drug Carriers; HPMA; Mice, Inbred BALB C; Tumor microenvironment; Animals; lidé; ženské pohlaví; taxoidy; Humans; zvířata; Drug delivery; myši inbrední C57BL; akrylamidy; myši; Mice, Inbred C57BL; nádory; nádorové buněčné linie; Mice; Female; nosiče léků; Docetaxel; Doxorubicin; Antineoplastic Agents